Kontribusi Power Tungkai dan Power Lengan Terhadap Kecepatan Jumping Servis Bola Voli Atlet Porda Kabupaten Sukabumi 2022 - Taufik Hidayat; Mulyana Mulyana; Nida'ul Hidayah (Jurnal Kepelatihan Olahraga, 2022)
The purpose of this study was to determine the contribution of leg power and arm power to the service jump speed results, to determine the contribution of leg power and arm power to the athlete's service jump results in Sukabumi Regency. The method used is descriptive. The sample used was 14 athletes using total sampling. Data analysis using correlate bivariate. Based on the results of the study 1) for the value of leg power on the speed of service jumping, R 0.589 was obtained with a sig value of 0.027 0.05, the magnitude of the significant contribution was 34.6%. 2) for the arm power at the service jump speed, the R value is 0.543 with a sig value of 0.045 0.05, the magnitude of the significant contribution is 29.5%. 3) for the simultaneous multiple correlation of leg power and arm power variables on the speed of service jumping, R2 is 0.602 and F is 8.773 with a sig value of 0.006 0.05 with a significant contribution of 60.2%. The results of the study are as follows: 1) Leg strength contributes 34.6% to service jump speed, 2) Arm strength contributes to service jump speed by 29.5%, 3) Leg strength and arm strength are simultaneously the same. the same contributed to the service speed jump by 60.2%.